ANTICONVULSANT EFFECT OF ISOLATED COMPOUNDS FROM THE LEAVES OF GLOBIMETULA BRAUNII ENGLER VAN TIEGH (LORANTHACEAE) IN MICE AND CHICKS (Jurnal Teknologi (Sciences & Engineering), 2024)
The anticonvulsant evaluation of globrauneine A (1), globrauneine C (2) globrauneine D (3), globrauneine F (4), lupeol (5), β-sitosterol (6), (1R,5S,7S)-7-[2-(4-hydroxyphenyl) ethyl]-2,6-dioxabi-cyclo [3. 3.1]-nonan-3-one (7), dodoneine (8), quercetin (9) and rutin (10) from Globimetula braunii leaves were analyzed with the aid of pentylenetetrazole-induced seizure test in mice (PTZ) and maximal electroshock seizure test in chicks (MEST), while the neurotoxicity was evaluated using the beam walking assay in mice. 50% of the tested mice were protected by Globrauneine A (1) and dodoneine (8) against PTZ-induced mortality. The mean onset of clonic spasm of the unprotected animals was increased by Quercetin (9) and also the mice were differentially protected against mortality. The tested compounds also produced significant (p<0.05) increase in the mean onset of seizure against pentylenetetrazole-induced seizure. The chicks were not protected by the tested compounds against MEST and the recovery time was not significantly reduced. In the beam assay, with the exception of dodoneine (8), the number of foot slips and the time taken to complete the task was not significantly changed by the tested isolated compounds, suggesting that the observed activities are not due to general CNS depression. The results suggest mild protective effects of these isolated compounds against seizure which might be useful in the control of petit mal epilepsy.